2020
DOI: 10.7554/elife.62456
|View full text |Cite
|
Sign up to set email alerts
|

Salivary and plasmatic oxytocin are not reliable trait markers of the physiology of the oxytocin system in humans

Abstract: Single measurements of salivary and plasmatic oxytocin are used as indicators of the physiology of the oxytocin system. However, questions remain about whether they are sufficiently stable to provide valid trait markers of the physiology of the oxytocin system, and whether salivary oxytocin can accurately index its plasmatic concentrations. Using radioimmunoassay, we measured baseline plasmatic and/or salivary oxytocin from two independent datasets. We also administered exogenous oxytocin intravenously and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
56
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 53 publications
3
56
2
1
Order By: Relevance
“…Finally, the half-life of OXT in blood is short, lower than 4 min [ 41 ], and the nature of lactation-induced release of OXT in blood is pulsatile [ 42 , 43 ]. On the contrary, despite the half-life of sOXT still being unknown, the most likely hypothesis is that OXT half-life in saliva is longer than OXT half-life in plasma [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the half-life of OXT in blood is short, lower than 4 min [ 41 ], and the nature of lactation-induced release of OXT in blood is pulsatile [ 42 , 43 ]. On the contrary, despite the half-life of sOXT still being unknown, the most likely hypothesis is that OXT half-life in saliva is longer than OXT half-life in plasma [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Participants completed their spiritual/religious faith questionnaire in 2015, whereas their saliva samples were collected in 2018. Although previous studies have suggested the individual stability of both peripheral oxytocin levels (Schneiderman et al, 2012;Feldman et al, 2013;Gordon et al, 2017) and religious beliefs (Koenig et al, 2008;Koenig, 2015), some studies argued that oxytocin levels could vary with each day (Martins et al, 2020). Therefore, in future studies, it is required to measure all indexes simultaneously and determine whether the same results are replicated or not.…”
Section: Limitation and Future Directionsmentioning
confidence: 99%
“…First, an important assumption is that the test-retest reliability of peripheral neuropeptide measures. However, there is poor week-to-week reliability of plasma or saliva oxytocin (Martins et al, 2020a) or plasma vasopressin (Quintana et al, 2017b;Stachenfeld et al, 1999), which is a closely related neuropeptide.…”
Section: Oxytocin Concentrations In Peripheral Fluids Are a Reliable Measure Of Oxytocin System Activitymentioning
confidence: 99%